Targeted transcriptomics reveals signatures of large-scale independent origins and concerted regulation of effector genes in Radopholus similis - Paulo Vieira (Public Library of Science (PLoS), 2021)
The burrowing nematode, Radopholus similis, is an economically important plant-parasitic nematode that inflicts damage and yield loss to a wide range of crops. This migratory endoparasite is widely distributed in warmer regions and causes extensive destruction to the root systems of important food crops (e.g., citrus, banana). Despite the economic importance of this nematode, little is known about the repertoire of effectors owned by this species. Here we combined spatially and temporally resolved next-generation sequencing datasets of R. similis to select a list of candidates for the identification of effector genes for this species. We confirmed spatial expression of transcripts of 30 new candidate effectors within the esophageal glands of R. similis by in situ hybridization, revealing a large number of pioneer genes specific to this nematode. We identify a gland promoter motif specifically associated with the subventral glands (named Rs-SUG box), a putative hallmark of spatial and concerted regulation of these effectors. Nematode transcriptome analyses confirmed the expression of these effectors during the interaction with the host, with a large number of pioneer genes being especially abundant. Our data revealed that R. similis holds a diverse and emergent repertoire of effectors, which has been shaped by various evolutionary events, including neofunctionalization, horizontal gene transfer, and possibly by de novo gene birth. In addition, we also report the first GH62 gene so far discovered for any metazoan and putatively acquired by lateral gene transfer from a bacterial donor. Considering the economic damage caused by R. similis, this information provides valuable data to elucidate the mode of parasitism of this nematode. Author summary Radopholus similis is considered to be among the top 10 most damaging plant-parasitic nematodes world-wide. The molecular dialogue established by plant-parasitic nematodes and the host plant is driven by secreted nematode proteins, also known as effectors. Here we use targeted transcriptomics to predict and validate the most comprehensive set of effectors for this plant-parasitic nematode. Contrary to long-held assumptions that migratory nematodes are less specialized plant-parasitic nematodes, we showed that the repertoire of effectors of this migratory nematode is largely complex and novel. Among the 30 new effector genes identified, 19 were pioneer genes without a priori putative function or annotation but highly expressed during plant interaction. The identification of a promoter motif element for a significant set of these effectors suggest a concerted regulation of these genes by the nematode. The increase knowledge of the effector repertoire of this economic important species not only contributes to the understanding of the mechanisms of parasitism employed by migratory nematodes, but will also allow the development of effector gene targeted strategies to control this nematode.